2019
DOI: 10.1088/1361-648x/aaf76b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen interaction with graphene on Ir(1 1 1): a combined intercalation and functionalization study

Abstract: We demonstrate a procedure for obtaining a H-intercalated graphene layer that is found to be chemically decoupled from the underlying metal substrate. Using high-resolution x-ray photoelectron spectroscopy and scanning tunneling microscopy techniques, we reveal that the hydrogen intercalated graphene is p-doped by about 0.28 eV, but also identify structures of interfacial hydrogen. Furthermore, we investigate the reactivity of the decoupled layer towards atomic hydrogen and vibrationally excited molecular hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
(67 reference statements)
0
5
0
Order By: Relevance
“…Second, the graphene-substrate interaction is relatively weak such that the graphene π-band is almost intact [7,8]. Actually, the electronic structure, which presents mini gaps and replica bands, can be tuned and chemically decoupled from the substrate by intercalation [9][10][11][12]. In this scenario, an atomic level structural characterisation of graphene grown on iridium (Gr/Ir) is fundamentally important to understand its electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the graphene-substrate interaction is relatively weak such that the graphene π-band is almost intact [7,8]. Actually, the electronic structure, which presents mini gaps and replica bands, can be tuned and chemically decoupled from the substrate by intercalation [9][10][11][12]. In this scenario, an atomic level structural characterisation of graphene grown on iridium (Gr/Ir) is fundamentally important to understand its electronic properties.…”
Section: Introductionmentioning
confidence: 99%
“…[6] One-thirdhydrogenated graphene (OTHG) has also been fabricated and found to exhibit anisotropic electronic properties. [7] By now, a large assortment of hydrogenated forms of graphene (HGr) with different carbon-to-hydrogen (C/H) ratios have been predicted [2,5,8] or fabricated [7,[9][10][11][12][13][14][15][16][17][18][19][20] . It has been found that the C/H ratio can be used to tune the band gap.…”
Section: Introductionmentioning
confidence: 99%
“…[7] By now, a large assortment of hydrogenated forms of graphene (HGr) with different carbon-to-hydrogen (C/H) ratios have been predicted [2,5,8] or fabricated. [7,[9][10][11][12][13][14][15][16][17][18][19][20] It has been found that the C/H ratio can be used to tune the bandgap. [9,17,21] Giant local enhancement of spin-orbit coupling has been predicted [22] and demonstrated when introducing small amounts, ≈0.01-0.05%, of hydrogen atoms.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogenated Gr has been synthesized and studied in several systems by controlled atomic H (H at ) exposure of single crystal surfaces [10][11][12]. For other 2D materials such as h-BN [13][14][15][16], borophene [6] and MoSe 2 [17] the reactivity towards H at has been investigated only very recently.…”
Section: Introductionmentioning
confidence: 99%